Fenchone, a monoterpene: Toxicity and diuretic profiling in rats - Bashir, Asifa; Mushtaq, Muhammad Naveed; Younis, Waqas; Anjum, Irfan (Frontiers in Pharmacology, 2023)
Fenchone is a monoterpene present in the essential oils of various plants, including Foeniculum vulgare and Peumus boldus. Previous studies confirmed the anti-inflammatory, antioxidant, wound-healing, antidiarrheal, antifungal, antinociceptive, and bronchodilator activities of fenchone. Owing to various pharmacological activities of Fenchone, the current research was designed to evaluate its diuretic activity along with toxicity profiling. For evaluating acute toxicity, OECD guideline 425 was followed in which a single dose of 2000 mg/kg was orally administered to rats. For evaluating the diuretic potential in rats, three doses of Fenchone (100, 200, and 400 mg/kg) were assayed in comparison to furosemide (15 mg/kg) as the standard drug, followed by measurements of urinary volume, urinary electrolytes, uric acid, and urinary creatinine in saline-loaded rats for 8 h. The acute toxicity study showed a significant increase in hemoglobin (Hb), red blood cells (RBCs), alkaline phosphatase (ALP), and alkaline transaminase (ALT) along with a significant decrease in serum triglycerides, cholesterol, and uric acid levels when compared with the control group. The oxidative stress parameter, superoxide dismutase (SOD), was increased in the heart and spleen. Nitrite (NO) and glutathione were significantly increased in the kidney. The acute diuretic effect of Fenchone (400 mg/kg) significantly increased the urinary output, electrolytes (Na+, K+, and Ca++), urinary creatinine, and urinary uric acid in a dose-dependent manner. The Na+/K+ ratio was remarkably higher in the treatment group than that of the control group. The diuretic index, saluretic index, and Lipschitz value were also calculated from electrolyte concentration and urinary volume measurements, and the values were significantly increased in rats administered with fenchone at 400 mg/kg dose. The current study concluded that fenchone is safe and has remarkable diuretic action.